Peningkatan profesionalisme guru teknologi kejuruan melalui keterampilan merancang dan mengembangkan multimedia interaktif offline - Wahid Munawar (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2011)
IMPROVING VOCATIONAL TEACHER TECHNOLOGICAL PROFESSIONALISM THROUGH SKILLS DESIGNING AND DEVELOPING OFFLINE INTERACTIVE MULTIMEDIATeaching learning in Vocational Schools are mostly Delivered in conventional method, rote learning, demonstration, and practicing using guide book. As indicated in teaching Teknologi Dasar teacher uses conventionsl method, although he/she still uses blackboard, trainer kits in two dimensions. Consequently, students have difficulties in coping conceptual concept that describing process and misconception is emerged. This verbalistic technology teaching will have implication on students inability to compete with other school leavers. Therefore, alternative strategy of learning need to be investigated in order to prepare students to work in work place through multimedia teaching. Innovative learning by using offline interactive multimedia will contribute on learning technology and it reduces misconception and verbalistic technology in school. Offline Interactive Multimedia was designed through five phases: (1) product analysis, (2) product development, (3) experts judgement and revision, (4) field validation, (5) revision and validation for wider subject and final product.